Actitud de los estudiantes en la realización de tareas de matemáticas en tercer año de bachillerato paralelo C,D,E del Colegio Técnico Pasaje sección vespertina del cantón Pasaje provincia de El Oro. - Nagua Jiménez, Luis Felipe (2014)
The attitude with which the student faces his academic commitment will determine the success or failure of his studies. However, family support and help from the teacher will help the student achieve his or her intellectual goals, even more so if he or she is dealing with subjects considered as complex as mathematics. For this reason, it was considered the reason for the present research the attitude of students of the Third Year of High School of Technical College Pasaje, of the Province of El Oro, to determine the appropriate way to enhance the active learning of mathematics.